The Effect of Physical Activity Level on the Low Back Pain Incidence Among Dentists in Yogyakarta City - Pambudi, Septiawan Tri; Adiningrat , Arya; Prastyo, Alfian Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Low back pain (LBP) is a complaint that dentists often encounter because of the tendency to work with static movements for a long duration of time. There are some indicated factors that may involve in the occurrence of the LBP, one of which is the level of physical activity. This study aimed to confirm and understand the association of physical activity level to the incidence of low back pain. The research method was analytical observation with a cross-sectional design. The study used questionnaires on physical activity level and low back pain which were distributed to 76 samples of dentists in the Yogyakarta City area. The data was further analyzed with a chi-square test. The results showed a value of 9.147 with degree of freedom 1 and significance of 0.002. This value is greater than the table's chi-square value of 3.841, which means that there was a significant proportion association between physical activity level and low back pain occurrence